Use of partial information to learn to read Chinese characters in non-native Chinese learners. (January 2023) - Liu, Yang; Zhang, Jie; Li, Hong
The ability to decode new words of varying degrees of orthographic-phonological mapping is an important word recognition skill across languages. Chinese characters represent three types of phonetic regularity: regular, semi-regular, and irregular depending on the degree of reliability of the pronunciation information provided by the phonetic component. This study investigated whether adult non-native Chinese learners can use partial phonological information encoded in semi-regular characters to learn the pronunciations of new characters. A total of 55 college students, enrolled in an intensive Chinese program with varying proficiency levels, were taught the pronunciations of 18 novel compound characters of three phonetic regularity types over three trials. Non-native Chinese learners of advanced and intermediate levels learned the pronunciations of regular characters (initial-same and final-same), which contain full information about pronunciation, and semi-regular characters (initial-different, final-same), which contain partial information about pronunciation, significantly better than irregular characters (initial-different and final-different), which contain misleading pronunciation information. The performance difference between semi-regular and irregular characters decreased over trials. Novice students demonstrated limited ability in using partial information to learn to pronounce characters compared to intermediate and advanced students. These results provide implications for effective character instruction for adult learners of Chinese with varying Chinese proficiency levels.